THE EFFECT OF JOB STRESS, JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE OF CV. CALANTHA PERMAI IN MANADO: PENGARUH STRESS KERJA, KEPUASAN KERJA DAN KOMITMEN OORGANISASI TERHADAP KINERJA KARYAWAN CV. CALANTHA PERMAI DI MANADO - Joshua J. Pelealu; Joyce J. Rares; Levianne J. H. Lotulung (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
This study delves into the repercussions of job stress, job satisfaction, and organizational commitment on the work performance of employees within CV. Calantha Permai, situated in Manado. Employing a quantitative research approach, the investigation utilizes a structured questionnaire survey as its primary data collection method, gathering responses from employees. Subsequently, the data is subjected to rigorous regression analysis. The findings of this study illuminate several critical insights. Firstly, job stress exerts a detrimental influence on employee performance, indicating a negative correlation between these two variables. Conversely, job satisfaction and organizational commitment exhibit a favorable relationship with performance, suggesting that as these factors increase, so does employee performance. These results have substantial implications for CV. Calantha Permai. The organization should consider the management of job stress levels, fostering higher levels of job satisfaction among its workforce, and cultivating greater organizational commitment as strategic objectives to optimize employee performance. These findings offer pertinent guidance to organizations seeking to enhance their competitive edge by prioritizing the well-being and commitment of their workforce.